Mutation analysis of the BRCA1 gene in Malaysian breast cancer patients - Balraj, P.; Khoo, A.S.B.; Volpi, L.; Tan, J.A.M.A.; Nair, S.; Abdullah, H. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2002)
Thirty patients with early onset breast cancer or familial breast cancer from Malaysia were analysed for germline mutation in the early onset breast cancer I gene (BRCA1). Direct sequencing of the entire coding region of BRCA1 identified a frameshift mutation, c.5447-5448insC (insC5447) (codon 1776 of exon 21) in a patient aged 32 of the Malay ethnic origin, who had no family history of breast and/or ovarian cancer. Eight polymorphisms (2201C > T, 2430T > C, P871L, E1038G, K1183R, 4427T > C, S1613G and IVS8-57delT) were identified in the samples tested.